The Written Text Analysis of Lexical Cohesion and Stylistic Choice of A Bahasa Indonesia Agony Letter and Its Responses - suseno, bambang (Universitas Ahmad Dahlan, 2020)
In order that the reader can get across the message of a written text clearly, the writer is responsible to maintain its coherence as it is one of the significant aspects of the text. A letter that deals with complaints of marriage problems, its inquiries of suggestions in solving them and its answers is the written text that is analysed in this article. The analysis is conducted to find out what elements are used in it. Coherence applied in this article is lexical cohesion such as synonyms, hyponyms and superordinates, and stylistic choice in the form of choice of words and sentence structures.